IEEE INFOCOM 2003. Twenty-Second Annual Joint Conference of the IEEE Computer and Communications Societies (IEEE Cat. No.03CH37
DOI: 10.1109/infcom.2003.1208671
|View full text |Cite
|
Sign up to set email alerts
|

Heavy tailed M/G/1-PS queues with impatience and admission control in packet networks

Abstract: Abstract-In this paper we analyze the M/G/1 processor sharing queue with heavy tailed services and with impatient customers. It is assumed that impatience depends on the value of the service required. We prove that a reduced service rate (RSR) approximation holds for estimating the sojourn time of a customer in the system, when the queue capacity is finite or infinite. This allows us to evaluate the reneging probability of customers with very large service times. We then use these results to investigate the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…Secondly, our results demonstrate that the negative performance impact of the heavy-tailed class can be reduced by limiting the number of simultaneously active users in the system. These findings reinforce some of the arguments made in [4,11] in favor of admission control for TCP flows. It is worth observing that in practice TCP time-out effects and user impatience may indirectly induce a limit on the maximum number of active flows (although the actual mechanics are quite different).…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Secondly, our results demonstrate that the negative performance impact of the heavy-tailed class can be reduced by limiting the number of simultaneously active users in the system. These findings reinforce some of the arguments made in [4,11] in favor of admission control for TCP flows. It is worth observing that in practice TCP time-out effects and user impatience may indirectly induce a limit on the maximum number of active flows (although the actual mechanics are quite different).…”
Section: Introductionsupporting
confidence: 89%
“…They further showed that the result is sharp, in the sense that the tail equivalence does not hold for Weibull distributions with a larger index parameter. Recently, Boyer et al [4] obtained a tail equivalence result for heavy-tailed PS queues with impatient users and admission control. In contrast to the remarkably explicit results for heavy-tailed PS queues, the delay asymptotics for light-tailed service requirements have remained largely intractable.…”
Section: Introductionmentioning
confidence: 99%
“…Define (5) Note that by definition R(x) = R 1 (x). With similar arguments as before, it is not difficult to show that (4) lim…”
Section: The Mig/1 Ps Queuesupporting
confidence: 62%
“…The large-deviations results of the present paper aim to give some insight into the introduction of admission control for elastic traffic in broadband packet networks; we refer to the paper Boyer et al [4] for more discussion in this direction. From a technical point of view, the main point of that paper is to make use of the relation IP'…”
Section: P' (V> X) Rv 1p' (B > X(1 -P))mentioning
confidence: 93%
“…figures 12,14,16,21). This is due to the fact that max-min fairness gives an absolute priority to flows with small bit rates.…”
Section: Resultsmentioning
confidence: 99%